2017
DOI: 10.3389/fpls.2017.01892
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Susceptibility to Anthracnose in the World Collection of Olive Cultivars of Cordoba (Spain)

Abstract: Anthracnose of olive (Olea europaea ssp. europaea L.), caused by Colletotrichum species, is a serious disease causing fruit rot and branch dieback, whose epidemics are highly dependent on cultivar susceptibility and environmental conditions. Over a period of 10 years, there have been three severe epidemics in Andalusia (southern Spain) that allowed us to complete the assessment of the World Olive Germplasm Bank of Córdoba, one of the most important cultivar collections worldwide.A total of 308 cultivars from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…The analysis of variance of mean disease severity and incidence under field conditions revealed highly significant differences (P≤0.001) among the genotypes. The three regions of study showed site variations on incidence and severity among the genotypes and from these results therefore, it is evident that disease incidence and severity differs in different locations and this is in agreement with studies made by Moral et al 2017. From the results, Busia had high incidence and severity of anthracnose on the selected common bean genotypes, followed by Bungoma and University of Eldoret.…”
Section: Incidences and Severities Of Anthracnose On Selected Common supporting
confidence: 86%
“…The analysis of variance of mean disease severity and incidence under field conditions revealed highly significant differences (P≤0.001) among the genotypes. The three regions of study showed site variations on incidence and severity among the genotypes and from these results therefore, it is evident that disease incidence and severity differs in different locations and this is in agreement with studies made by Moral et al 2017. From the results, Busia had high incidence and severity of anthracnose on the selected common bean genotypes, followed by Bungoma and University of Eldoret.…”
Section: Incidences and Severities Of Anthracnose On Selected Common supporting
confidence: 86%
“…The establishment of the Olive World Germplasm Bank in Córdoba (Spain) has enabled direct comparison of cultivars, contributing to the solution of homonymy and synonymy problems. It is a valuable source of germplasm which may help in the current expansion projects of the crop to other regions (Moral et al ., ). It also enables the performance of olive anthracnose resistance screening experiments.…”
Section: Host Resistance and Plant–pathogen Interactionsmentioning
confidence: 97%
“…Based on the same collection, Moral et al . () analysed 308 cultivars from 21 countries, 21% of which were classified as highly susceptible, 27% as susceptible, 21% as moderately susceptible, 20% as resistant and 10% as highly resistant. These authors selected cultivars as representative of each resistance class: ‘Ocal’, highly susceptible; ‘Lechín de Sevilla’, susceptible; ‘Arbequina’, moderately susceptible; ‘Picual’, resistant; ‘Frantoio’, highly resistant.…”
Section: Host Resistance and Plant–pathogen Interactionsmentioning
confidence: 99%
“…Picual presented infection symptoms, on fruit mesocarp, only after 72 hai. The fruit ripeness increases the fruit susceptibility to pathogen infection, with the unripened (or developing) fruit being tolerant to the C. acutatum infection [9,13]. According to the total phenolic measures (Figure 3), the cultivars respond to the infection by increasing the level of phenols at 16 hai (crop year 2016) and 48 hai (crop year 2017) directly associated with the elicitation increases of the PAL enzyme activity (Figure 2).…”
Section: Discussionmentioning
confidence: 99%